Calidad biológica del agua en un sistema de cultivo de peces de consumo utilizando macroinvertebrados acuáticos, San Martín-Perú, 2018 - Del Aguila Panduro, Erick Alberto (2022)
The water in the ponds and drainage of a fish farming system constantly receives nutrients from organic fertilization, unconsumed food and fish excreta, which can generate changes in the biological quality of the water. This is why this study aimed to determine the biological quality of water in a fish farming system for consumption, through the richness, abundance and presence of aquatic macroinvertebrates sensitive and/or tolerant to changes in the environment. It was carried out from September to November 2018, at the Carlos Miguel Castañeda Ruiz Research Center of the Peruvian Amazon Research Institute, San Martín, Peru, which has aquaculture infrastructure for research, management of broodstock and production of Amazonian fish fingerlings. Three study zones were established, zone 1: water inlet from a stream, Zone 2: management pond for fish broodstock for consumption, and Zone 3: water drainage back into the stream. The collections were made by applying the D-type net drag technique and the water quality was obtained by applying the nBMWPper index. The richness was composed of 04 phyla, 10 classes, 19 orders and 48 families, the most diverse phylum was Arthropoda and the orders with the largest number of families were Diptera and Hemiptera. The abundance was 6566 individuals, Hidrobiidae and Corbiculidae recorded the largest number; zone 2 was the most abundant and significantly different from the other zones. 33 families between sensitive and tolerant to changes in the biological quality of the water were registered; the same as in the three study areas was good. In conclusion, the aquaculture activity in the studied area has not generated permanent changes in the biological quality of the water.